The Associations Between White Matter Disruptions and Cognitive Decline at the Early Stage of Subcortical Vascular Cognitive Impairment: A Case–Control Study - Qiao, Yanan; He, Xuwen; Zhang, Junying; Liang, Ying; Shao, Wen; Zhang, Zhanjun; Zhang, Sihang; Peng, Dantao (Frontiers in Aging Neuroscience, 2021)
Objective: Emerging evidence suggests that white matter (WM) disruption is associated with the incidence of subcortical vascular cognitive impairment (SVCI). However, our knowledge regarding this relationship in the early stage of SVCI is limited. We aimed to investigate the associations between WM disruptions and cognitive declines at the early stage of SVCI. Method: We performed a case-control study, involving 22 cases and 19 controls. The cases were patients at the early stage of SVCI, which was defined as subcortical ischemic vascular disease with normal global cognitive measures (pre-SVCI). The controls were healthy people matched by age, sex, and education years. We assessed the differences in a battery of neuropsychological tests between the two groups, investigated the diffusion changes in 40 WM tracts among the participants via an atlas-based segmentation strategy and compared the differences between the cases and controls by multiple linear regression analysis. We then evaluated the relationships between diffusion indices and cognitive assessment scores by Pearson’s correlation. Results: The pre-SVCI group exhibited significant differences in the Montreal cognitive assessment (MoCA), Rey-Osterrieth Complex Figure (R-O)-copy and Trail Making Test (TMT)-B test compared with the controls. Compared with the controls, some long associative and projective bundles, such as the right anterior corona radiata (ACR),the right inferior fronto-occipital fasciculus (IFOF) and the left external capsule (EC) were extensively damaged in cases after Bonferroni correction (P <0.05/40). Damages to specific fibers, such as the right ACR ,IFOF and posterior thalamic radiation (PTR) exhibited significant correlations with declines in MoCA, R-O delay and the Mini-Mental State Examination (MMSE) respectively after Bonferroni correction (P<0.05/14). Conclusions: Long WM tracts, especially those in right hemisphere, were extensively damaged in the pre-SVCI patients and correlated with declines in executive functions and spatial processing. Patients of pre-SVCI are likely at an ultra-early stage of SVCI, and there is a very high risk of this condition becoming SVCI.